PHARMACOGNOSTIC AND PHYTOCHEMICAL SCREENING OF COCCULUS PENDULUS Diels. STEM AND ROOT - M. Nafees1; S. Ullah; Barkatullah; A. Javaid; Shumaila (Journal of Animal and Plant Sciences, 2020)
Cocculus pendulus Diels. belongs to family Menispermaceae locally known as “Parwatti” is a part of medicines against jaundice, yellow fever, leprosy, syphilis and as an aphrodisiac. To authenticate the C. pendulus from adulterations, in the present study the stem and root has been evaluated for different pharmacognostic studies. Morphologically the plant is dioecious, woody climber (Liana) and about 4-8m tall. The macroscopic study showed that stem is cylindrical in shape, characteristic odor, acceptable taste and brittle fracture while the root is irregular in shape with characteristic odor and bitter taste. Histologically both plant parts showed typical dicot anatomy. Preliminary phytochemical screening showed the presence of proteins, carbohydrates, alkaloids, tannins, saponins, steroids, flavonoids, glycosides and phenolic compounds in both plant parts. Quantitatively highest amount of sterols 85.32±2.42mg/g followed by alkaloids 30.45±0.32mg/g in root while stem with 71.43±1.24mg/g amount of sterols and 21.47±0.54mg/g alkaloids has been recorded. Fluorescence analysis showed diverse colors by treating with different reagents at ordinary and UV light. Powdered drug study and percent extractive values determination were also carried out. Pharmacognostic studies will be helpful in the standardization and authentication of the species from adulteration as the above studies has been carried out for the first time for the said plant.
Keywords: Cocculus pendulus; fluorescence analysis; pharmacognosy; phytochemical screening